Effect of Ectoparasitism on Length-Weight Relationship and Condition Factor of Five Fish Species in River Penna, Kadapa, Andhra Pradesh - Vankara, Anu Prasanna (Asian Journal of Biological and Life Sciences)
Objectives: This study investigates the impact of ectoparasitic infections on Length-Weight Relationships (LWR) and condition factor of five freshwater fishes of River Penna, Kadapa, Andhra Pradesh from three sampling sites between March, 2017 to March, 2018. Materials and Methods: Sampled fish were examined for ectoparasites and their associated pathologies according to standard protocols. Their lengths and weights were measured to determine the length-weight relationships and condition factors. A total of 465 fishes (122 Labeo calbasu, 45 Mastacembelus armatus, 70 Mystus vittatus, 133 Oreochromis niloticus and 95 Wallago attu) were sampled. Results: Overall, 80% of the sampled fishes were infected with ectoparasites; Labeo calbasu (75.7%), M. armatus (91%), M. vittatus (77.1%), O. niloticus (68.4%) and W. attu (98.9%). The prevalence rates were significantly influenced by size (p=0.960, χ2= 0.6256, non-significant) and weight (p<0.00001, χ2= 72.66, significant) and negative allometric growth patterns (b < 2) were observed irrespective of the parasitic status of the fishes. There was strong positive correlation between the length and weight of the fish species (r> 0.92), except for M. armatus (r> 0.066). The mean condition factor (K) varied between 1.00 to 3.56 throughout in the study according to sex, species, season and ectoparasitic status of the fish. The results indicated that K factor of M. armatus, W. attu and M. vittatus was higher (K> 2) than L. calbasu and O. niloticus (K< 2). Male fishes showed slightly higher K factor than the female fishes during the summer and rainy seasons than winter season. The Condition Factor (K) of infected and uninfected fishes showed that the K factor of uninfected fishes was somewhat greater than that of infected fishes, with the exception of the K factor of infected L. calbasu, which was slightly higher than the uninfected L. calbasu. Conclusion: The present investigation concluded that ectoparasite infection has a substantial impact on LWR and condition factors of fish from the River Penna. The control of ectoparasitic infection of cultured fishes is vital for improved conditions, health and production yields in fishery sectors in India.
Keywords: Allometric growth; Condition factor; Ectoparasitism; Fish Health; Length-weight relationship; River Penna.